MODEL ALOKASI SUBSIDI DANA APBD DAN CSR UNTUK OPTIMASI PENGADAAN MESIN KOMODITAS LELANG: STUDY KASUS - Zainida, Maya Revanola; Sutopo, Wahyudi; Hisjam, Muhammad (Jurnal Ilmiah Teknik Industri, 2023)
Procurement of machinery is a facilitation to overcome auction problems in accordance with the strategic plan of the Dinas TPHPKP to maintain and improve the quality or quality of commodities so as to increase the selling value. To carry out this facilitation with limited funds, other sources of subsidized funds are needed, the government needs tools to determine the nominal funding decision, the decision to place the machine, and the feasibility study of the model. Based on surveys, interviews, and previous research, the research data was processed using goal programming with Excel and ILOG CPLEX. This study chooses scenario three as the optimal scenario because the nominal subsidy of funds is smaller than scenarios one and two, but results in machine option decisions on each quality improvement function with a positive benefit deviation value of Rp. 20,014,000. This study succeeded in formulating a fund allocation model, determining five locations for placing machines and stating the feasibility of a fund allocation model with a Benefit Cost Ratio value of 1.49. Future research is expected to be able to consider the cost of energy consumption in the next use of the machine, consider the form of village assets as a candidate for placing the machine, and calculate other feasibility study parameters.